Faktor Risiko Kejadian Anemia Pada Ibu Hamil Di Klinik Utama Anny Rahardjo Jakarta Timur : Risk Factors for Anemia in Pregnant Women at Anny Rahardjo Main Clinic East Jakarta - Tambaru, Vira Alya (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Anemia is a condition where there is a decrease in hemoglobin, hematocrit, and erythrocyte counts below normal values. The prevalence of anemia in DKI Jakarta Province is 43.5%. The incidence of anemia is caused by low awareness of consuming iron tablets, and a lack of nutritious food intake. Iron supplementation is an effective way because the iron content is complemented by folic acid which can prevent anemia due to folic acid deficiency. Diet, adherence to consuming iron tablets (Fe), and the role of health workers are risk factors that cause anemia in pregnant women. Methods: An analytic observational study with a cross-sectional approach. The sample in this study was 110 people. The sampling technique was consecutive sampling using inclusion criteria: pregnant women with gestational age in the second and third trimesters and who had received iron (Fe) tablets. Data analysis with Chi-Square test and Odd Ratio (OR) calculation. Results: There is a significant relationship between diet and the incidence of anemia (p-value is 0,047; OR = 3,486), the compliance of Fe tablet consumption with the incidence of anemia (p-value 0,000; OR = 296), and the role of health workers with the incidence of anemia (p-value is 0,005; OR = 10,304. Discussion: In this study, it was proven that the diet, adherence to iron (Fe) consumption, and the role of health workers in the incidence of anemia in pregnant women.